Wykluczenie bonum sacramenti w opublikowanych wyrokach Trybunału Roty Rzymskiej z 2004 r. - Góralski, Wojciech (Ius Matrimoniale, 2014)
One of nullity titles which is difficult to establish in the canonic process of nullitatis matrimonii is the exclusion of the marriage indissolubility (can. 1101 § 2). The significant issue here is to establish – at the moment of the marriage conclusion – the positive act of will of the betrothed focused on (in one of possible ways) the marriage indissolubility. In the reviewed published judgments of the Roman Rota of 2004 a tendency to strengthen principles worked out by this apostolic tribunal regarding both the method of bonum sacramenti exclusion and the character of the positive act of will, as well as proving this exclusion in an individual case, can be noticed.